Developing Manipulative Basic Movement Learning Model Based on Traditional Games in Elementary Schools - Hendriana Sri Rejeki; Humaedi Humaedi; A. Ardiansyah (AT-TA'LIM, 2022)
This study aims to develop manipulative basic movement learning models based on tradition games at Elementary schools. Research and development method adopted from Borg and Gall was used. The effectiveness of the application of the manipulative basic motion learning model and catch and capture in these students used the "t-test" technique. Before the data were analyzed, the normality test was carried out on the pretest and posttest results of the basic motion manipulative and catch-and-catch using the Kolmogorov Smirnov test at the real level Î± = 0.05. The results of the manipulative basic motion of throwing catch between the pretest and posttest were obtained at a value of -24,645 at a significance of 0,000. So it can be concluded that the increase in the basic manipulative movement ability of throw and catch before and after learning has increased significantly. The contribution of the basic manipulative motion learning model of catch and capture is 42.21% based on the effectiveness test data at SD Tanamodindi and SD Inpres Lasoani.